ln(5-3)=ln(5)-ln(3)

Simple and best practice solution for ln(5-3)=ln(5)-ln(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(5-3)=ln(5)-ln(3) equation:


Simplifying
ln(5 + -3) = ln(5) + -1ln(3)

Combine like terms: 5 + -3 = 2
ln(2) = ln(5) + -1ln(3)

Reorder the terms for easier multiplication:
2ln = ln(5) + -1ln(3)

Reorder the terms for easier multiplication:
2ln = 5ln + -1ln(3)

Reorder the terms for easier multiplication:
2ln = 5ln + -1 * 3ln

Multiply -1 * 3
2ln = 5ln + -3ln

Combine like terms: 5ln + -3ln = 2ln
2ln = 2ln

Add '-2ln' to each side of the equation.
2ln + -2ln = 2ln + -2ln

Combine like terms: 2ln + -2ln = 0
0 = 2ln + -2ln

Combine like terms: 2ln + -2ln = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| c(x)=7x+569 | | 52=c-46 | | x(x+8)-(25x+3x)=0 | | (-7+9i)+(2-10i)= | | -3x-2y+z=11 | | 6x-77+7x+11=4x-60+3x | | 12x-45=26-3x-4 | | 5x^2+2c+7=0 | | r-46=15 | | 6x-77-7x+11=4x-60-3x | | 30=3v | | x=3-1y | | 7=56j | | 750-50x=-185 | | 2ln(7x)=5 | | y-4.1=5.4 | | a^2+12a-21=0 | | X+(11)=13 | | 3b-5=-44 | | 42x^2-18x= | | ln(5+3)=ln(5)+ln(3) | | E-14=0 | | 21=b-6 | | c+7=9 | | y=20(.682) | | y=20(1.025) | | a+4=35 | | 8(1-3x)=7(3x-1) | | x^2-mx-(m^2-5)=0 | | 4y-9=11y-23 | | (5-2i)-(3+3i)= | | y=95+15x |

Equations solver categories